(untitled) (Research, Society and Development, 2021)
Objective: to analyze the quality of life of informal elderly caregivers associated to their sociodemographic profile and health conditions. Methods: this is a quantitative, descriptive, cross-sectional research, carried out from March to May 2021, with 22 informal workers being evaluated. The data was analyzed using simple descriptive statistics and ANOVA. Results: it was found that among the 22 respondents, 90.9% were women, with ages ranging from 20 to 78 years, having most of them reported to be single (45.5%). Regarding level of education, 45.5% completed high school and 12.8% had a graduate degree. Of these 45.5% of respondents had pre-existing conditions, with the following conditions being identified within this study: asthma, heart disease, hypothyroidism, diabetes, hypertension, osteoporosis, and knee problems. Results also show that 59.1% reported never having sought psychological help, and 59.01% practiced physical activities regularly. Furthermore, final results also presented a significant difference between the physical and social relations domains of the WHOQOL-bref under the divorced and caucasian categories. Conclusion: this research aims to contribute tô new knowledge in the area of informal elderly caregivers and enable a better understanding of vulnerabilities in the quality of life of this population.